Public perception of e-money in the perspective of marketing communication strategy (Bandung) - Raharta, Rayasari; Hudrasyah, Herry (The Indonesian Journal of Business Administration, 2016)
In 2014 Bank Indonesia issued National Movement of Non-Cash Payment, which aims to raise public awareness about the use of non-cash payment system. The purpose of this study was to determine the public perception of the level of trust, comfort and safety of electronic money as well as the readiness of the people of Bandung to accept electronic money as a daily payment instrument. The method used in this research is qualitative as well as quantitative. From the analysis of consumers researcher found that the need to improve public perception of the level of trust, comfort and safety in using electronic money. The proposed solution to improve consumer perceptions about the level of trust is using marketing communication mix, to increase comfort researcher proposed product innovations, and to improve safety researcher proposed to improve security system of e-money and to implement new regulation. This approach is expected to improve consumers' perceptions of electronic money and also improve people's decision in the reception electronic money as daily payment instrument.